2019
DOI: 10.1177/1093526618824469
|View full text |Cite
|
Sign up to set email alerts
|

Early Bilateral Gonadoblastoma Associated With 45,X/46,XY Mosaicism: The Spectrum of Undifferentiated Gonadal Tissue and Gonadoblastoma in the First Months of Life

Abstract: 45,X/46,XY mosaicism is one of a heterogenous group of congenital conditions known as differences (disorders) of sex development (DSD) that results in abnormal development of internal and external genitalia. Patients with DSD, particularly those with segments of the Y chromosome, are at increased risk for germ cell tumors including gonadoblastoma. Gonadoblastoma is a neoplasm comprised of a mixture of germ cells and elements resembling immature granulosa or Sertoli cells with or without Leydig cells or lutein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It is interesting that, compared with that of sex chromosomal mosaicism, we found an increased ratio (16.07%, 9 of 56) of unbalanced embryos involving parental abnormal karyotypes in autosomal structural abnormality mosaicism. Of the 56 embryos, 5 (8.93%) exhibited a 16q21-q24.3 copy number abnormality that was associated with the parental karyotype mos.46,XY,ctg(16)(q22) [8]/ 46,XY[64], and 4 (7.14%) exhibited 46,XX,dup(8p23.1-8p11.21) and 46,XY,del(8p22-8p11.21), which were related to the parental karyotype mos.47,XY,del(8)(p23p10),þ r(8)(p23p10)[55]/46,XY,del(8)(p23p10) [5]. In addition, 8 (14.29%) exhibited de novo autosomal abnormalities.…”
Section: Ngs Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that, compared with that of sex chromosomal mosaicism, we found an increased ratio (16.07%, 9 of 56) of unbalanced embryos involving parental abnormal karyotypes in autosomal structural abnormality mosaicism. Of the 56 embryos, 5 (8.93%) exhibited a 16q21-q24.3 copy number abnormality that was associated with the parental karyotype mos.46,XY,ctg(16)(q22) [8]/ 46,XY[64], and 4 (7.14%) exhibited 46,XX,dup(8p23.1-8p11.21) and 46,XY,del(8p22-8p11.21), which were related to the parental karyotype mos.47,XY,del(8)(p23p10),þ r(8)(p23p10)[55]/46,XY,del(8)(p23p10) [5]. In addition, 8 (14.29%) exhibited de novo autosomal abnormalities.…”
Section: Ngs Resultsmentioning
confidence: 99%
“…Traditionally, chromosomal mosaicism is detected with karyotyping, and the mosaic ratio of different body tissues may be different. Although chromosomal mosaicism does not have s clinical impact in most cases, there are still some studies showing that the altered clinical phenotypes can be caused by mosaicism (5). However, it is very difficult to predict the clinical outcome of mosaic patients simply based on mosaic rate and the genotype-phenotype correlation (6).…”
mentioning
confidence: 99%
“…6 Gonadoblastomas and other gonadal neoplasms have a prevalence of up to 40% in 45,X/46,XY patients. 7 The presence of the gonadoblastoma (GBY) locus near the Yq centromere in 45,X/46,XY females predisposes to development of such neoplasms. 6,8,9 In particular, the Testis-specific Y-encoded protein 1 (TSPY) gene within the GBY region is thought to promote germ cell tumors in individuals with gonadal dysgenesis.…”
Section: Discussionmentioning
confidence: 99%
“…12 In males, germ cell tumors are more often associated with intra-abdominal gonads. 7 It has been suggested that 45, X/46,XY males with nearly normal external genitalia may be assessed periodically by ultrasound or physical palpation of the gonads. 6 However, dysgenetic gonads in any individual with Y chromosome increases the risk of gonadoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…109,124 Karyotypic analysis shows almost always the presence of Y chromosome, usually as 45, X/46, XY mosaicism or 46, XY. 126,127 The testis-specific protein in the GBY region of the Y chromosome, which contains gene encoding for testis-specific Y-encoded protein, has been linked to the development of gonadoblastoma and dysgerminoma/seminoma. 127,128 The sex-determining gene Y (SRY) on Y chromosome also plays some role in the development of gonadoblastoma.…”
Section: Gonadoblastomamentioning
confidence: 99%